The syntheses and investigation of the system CaTiSiO5 - CaSnSiO5 - R. A. Grigoryan; L. A. Grigoryan (ՀՀ ԳԱԱ հրատ.)
In the persisting message are brought results x-rays, UR studies of the multi-components system CaTiSiO5 - CaSnSiO5 at 1173 K and electro physical characteristics of formed hard solutions. Samples of CaTi1-хSnхSiO5 ware synthesized from oxides of appropriate metals in hydrogen - oxygen flames low temperature plasma [2] and classical ceramic technology. The X-ray data identification, which was realized with use parameters, provided in work [3] , shows, the CaTiSiO5 crystallizes in monoclinic structure. The Ca2+ Ions are located inwardly polyhedral emptiness formed by seven oxygen atoms, formed by oxygen atoms of the octahedral TiO6 and tetrahedral SiO4.
Keywords: Chemistry